Elearning and digital publishing (Springer, 2006)
"The book’s three main parts provide a framework that points out the relationships between information literacy, e-learning, and digital publishing. … I think anyone who wants to deploy modern publishing and learning projects at his or her university will find useful information in this book. … The book will appeal to a range of professionals who work in higher education libraries, university teachers, university policy makers, and staff who work in university publishing presses wishing to understand others experiences." (Patriciu Victor-Valeriu, Computing Reviews, December, 2006)